(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the importance of teaching English on little classes, different ways and methods using during the lesson. It can develop children’s basic communication abilities in the language. Communication abilities need to stimulate as early as possible. Teaching English also encourages enjoyment and motivation for language learning especially when it is in fun way. Teaching young learners is quite challenging and teachers need to be creative. This article also deals with young children’s foreign language acquisition and learning within the scope of the very early stages of the school system. Speech, language, and communication are critical areas of development for children. They play a vital role throughout our lives, helping us to understand what is going on around us, communicate our basic needs and feelings, hold conversations, think and learn, develop relationships,solve problems, and more.